Guía metodología para enseñar nomenclatura de compuestos inorgánicos mediante las tic para estudiantes de bachillerato de la Unidad Educativa Gonzol, provincia de Chimborazo período 2022. - Daquilema Aucanshala, José Manuel (2026)
This study, entitled "Methodological Guide for Teaching Nomenclature of Inorganic Compounds Using ICT for High School Students at the Gonzol Educational Unit, Chimborazo Province, 2022 Period," addressed the problems of teaching inorganic chemistry in a rural context with limited access to educational resources. The nomenclature of inorganic compounds posed significant challenges for students, who often resorted to memorization without achieving a deep understanding. The main objective of this research was to design a teaching guide based on Information and Communication Technologies (ICT) that would facilitate the teaching-learning process of chemical nomenclature. To this end, a quantitative approach with a non-experimental design was adopted, administering surveys to first-year high school students to determine their perceptions of the use of ICT in chemistry teaching. The results demonstrated students' interest in digital tools and their positive impact on motivation and understanding of chemical concepts. The findings confirmed that the integration of ICTs in inorganic chemistry teaching promoted meaningful learning. The methodological proposal designed was shown to improve students' academic performance and autonomy. It was concluded that the use of interactive digital resources, such as simulators and educational platforms, represented an effective alternative for optimizing the teaching of chemical nomenclature in technologically imited environments.